2017
DOI: 10.1186/s12884-017-1408-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of vitamin D in pre-eclampsia: a systematic review

Abstract: BackgroundThe etiology of pre-eclampsia (PE) is not yet fully understood, though current literature indicates an upregulation of inflammatory mediators produced by the placenta as a potential causal mechanism. Vitamin D is known to have anti-inflammatory properties and there is evidence of an inverse relationship between dietary calcium intake and the incidence of PE. Evidence of the role of vitamin D status and supplementation in the etiology and prevention of PE is reviewed in this article along with identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 116 publications
0
82
0
4
Order By: Relevance
“…Also, a significantly higher percentage of patients (75%) had an insufficient level of 25 (OH)-D compared with controls (53.7%, P = 0.003). 5 In a study from India, the maternal 25 (OH)-D concentration was negatively associated with blood pressure and the risk of preeclampsia; although, the severity of preeclampsia was not associated with vitamin D status. Consistent with our findings, it has been reported that there is a significant inverse association between systolic blood pressure and the level of 25 (OH)-D among adults.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Also, a significantly higher percentage of patients (75%) had an insufficient level of 25 (OH)-D compared with controls (53.7%, P = 0.003). 5 In a study from India, the maternal 25 (OH)-D concentration was negatively associated with blood pressure and the risk of preeclampsia; although, the severity of preeclampsia was not associated with vitamin D status. Consistent with our findings, it has been reported that there is a significant inverse association between systolic blood pressure and the level of 25 (OH)-D among adults.…”
Section: Discussionmentioning
confidence: 98%
“…However, the severity of preeclampsia was not related to the vitamin D level. 5 An inverse relationship between the plasma levels of 25 (OH)-D and increased risk of developing hypertension 17 and essential hypertension have been reported. Further, the insufficient level of vitamin D (<20 ng/mL) compared with sufficient level (20-30 ng/mL) resulted in significantly higher systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations